Influence of microcrack types on macroscopic cracking of sandstone under freeze-thaw erosion. - Yanan Sun; Bing Liang; Junzu Ma; Jiaxu Jin; Daoliang Liu (PLoS ONE)
Freeze-thaw erosion is a common hazard in cold region engineering, which is capable of generating a large number of microcracks inside the rock mass. However, the effect of different forms of microcracking on the macrocracking characteristics of sandstones under freeze-thaw erosion conditions has not been elucidated. Hence, the effect of microcracking on macrocracking under freeze-thaw cycling conditions is analysed by means of a combination of acoustic emission tests and numerical simulations. The results show that the peak strength, modulus of elasticity and longitudinal wave velocity of the sandstone produced a decrease with the increasing degree of freeze-thaw erosion. When the freeze-thaw cycle reached 80 times, the ringing counts changes significantly, showing a continuous accumulation trend. The trend of b value shows that microcracking of rock samples with high degree of freeze-thaw erosion is a continuous process of accumulation. The percentage of RA and AF indicates a shift in the cracking pattern from shear to tensile as the rock specimens are subjected to an increasing number of freeze-thaw cycles. Based on a model of sandstone after freeze-thaw erosion, it is concluded that inhomogeneous variations in the displacement and force chain fields of the particles lead to different modes of fracture extension. Finally, the mechanism of the influence of along-crystal microcracking and through-crystal microcracking on the macroscopic fracture of sandstone is discussed.